Internal Governance Mechanisms and Performance of Microfinance Institutions in Togo - Mowu, Kofi; Boubacar, Hamadou (Archives of Business Research, 2023)
Despite the boom in microfinance in Togo, the sector is seriously shaken by serious crises that threaten its performance and cast doubt on its sustainability. To explain performance crises to which microfinance institutions are subject, governance is regularly mentioned. This paper aims to identify internal governance mechanisms that can influence microfinance institutions’ performance in Togolese context. It is found out at the end of this paper that board of directors (the board size, presence of women on the board, duration of directors’ term of office and frequency of board meetings) influences financial and social performance of MFIs. On the contrary, the fact that MFI belong to a network or not, and its legal status have no effect on its performance.